Development of adaptive mechanisms of budget planning in the field of marketing activities in a turbulent economic environment - A. A. Sazonov; M. V. Sazonova (Вестник университета)
The article is devoted to the development of complex adaptation mechanisms in the field of financial planning of the organisation of marketing activities in a turbulent economic model, in which large economic systems have a certain asymmetry of the relationship between the dynamics of the growth of the size of the economy and the transformation of degrees of freedom within the organisation of economic activity. The authors clarified the concept of “planning in marketing activities” in terms of issues related to its adaptation to changing environmental conditions, which made it possible to introduce a modern concept: “flexible digital marketing”. An extensive classification of changes in the field of marketing has been given depending on the level of scale of changes in marketing activity plans at different time stages of planning. The authors propose an updated approach to the organisation of marketing activity planning processes based on network modeling, which is presented as a complex set of knowledge on the transformation of developed strategies and plans of marketing activities to abrupt changes. A classification of network planning methods in the field of marketing activities has been compiled, taking into account hypothetical changes in objects within the framework of developed marketing strategies.